The Effect of Work Motivation On The Work Quality Of Employees at PT. Agro Sinergi Nusantara - Rika Suprina; Chairiyaton Chairiyaton (Ridwan Institute, 2021)
The purpose of this study is to determine the effect of work motivation on the quality of work of employees at PT.Agro Sinergi Nusantara. Data collection methods used are: Observation, documentation and interviews. The data analysis method used is a qualitative descriptive analysis model. The results showed that the quality of work of employees is very dependent on the motivation given by the leadership. Because the leadership has provided appropriate motivation, the quality of the work of its employees continues to increase. This shows that there is a relationship between motivation and the quality of employees' work, which is very reciprocal, meaning that an increase in the quality of employees' work will have a positive effect on business income and will support the company's profits very large. Suggestions in this study are for the leadership of PT. Agro Sinergi Nusantara Meulaboh to have been able to provide appropriate motivation even though the motivation given must be maintained and further improved so that employees continue to improve performance in order to produce more optimal work results in accordance with what has been expected. by the later leadership for future researchers who take similar themes, it is better to add a longer research period to produce more significant data.